Geschichte im Roman / Roman in der Geschichte - Klaus-Detlef Müller (Recherches Germaniques)
In his novel Success [Erfolg], Feuchtwanger satirically draws on social constellations and political events in the early years of the Weimar Republic. Consequently, it seemed natural to read the novel as ‘roman à clef,’ which, however, has proven unsatisfactory. The historical references, in particular to the Munich Putsch of 1923, are blended into the fictive plot and its rules, which interprets their non-sensical nature in a historico-philosophical manner. In so doing, a distinct, autoreferential type of historical novel comes into being. Based on narratological means and their fictional self–reflection, this new type is suitable to generate a ‘plausible’ explanation for the events whose absurdity it exposes.